Gas6 Attenuates Sepsis-Induced Tight Junction Injury and Vascular Endothelial Hyperpermeability via the Axl/NF-κB Signaling Pathway - Ni, Jingjing; Lin, Miaotong; Jin, Yangjie; Li, Jiajia; Guo, Yayong; Zhou, Jindong; Hong, Guangliang; Zhao, Guangju; Lu, Zhongqiu (Frontiers in Pharmacology, 2019)
Vascular endothelial functional dysregulation and barrier disruption are involved the initiation and development of sepsis. Growth arrest-specific protein 6 (Gas6), one of the endogenous ligands of TAM receptors (Tyro3, Axl, and Mertk), is confirmed to have beneficial functions in hemostasis, inflammation, and cancer growth. Here, we demonstrated the protective effects of Gas6 on multi-organ dysfunction syndrome (MODS) in sepsis and the underlying mechanisms. We investigated Gas6 ameliorated MODS by inhibiting vascular endothelial hyperpermeability in a mouse model of sepsis. Additionally, in vitro, under lipopolysaccharide (LPS) stimulation in vascular endothelial cells, Gas6 attenuated vascular endothelial hyperpermeability by reinforcing the tight junction proteins occludin, zonula occludens-1 (ZO-1) and claudin5. Furthermore, Gas6 substantially suppressed NF-κB p65 activation. In addition, blocking the Gas6 receptor, Axl, partially reduced the protective effect of Gas6 on the vascular endothelial barrier and diminished the inhibitive effect of Gas6 on NF-κB p65 activation. Taken together, this study suggests that Gas6 has a protective effect on MODS in sepsis by inhibiting the vascular endothelial hyperpermeability, alteration of tight junction and that the Axl/NF-κB signaling pathway underlies these effects.